A retrospective stated preference approach to assessment of coastal infrastructure investments: An application to Barbados - Onil Banerjee; Kevin Boyle; Cassandra T. Rogers; Janice Cumberbatch; Barbara Kanninen; Michele Lemay; Maja Schling (Inter-American Development Bank (IDB), 2016)
Ex-post economic impact evaluations are standard requirements for loans and grants from multilateral international development institutions. In many cases, however, lack of sufficient baseline or historical data, or the very nature of the investment itself renders orthodox economic impact evaluation approaches unviable. Nonetheless, evaluations are required to provide an indication of the benefits generated by the investment and insights for future program design. Addressing this challenge, this paper develops an ecosystem service, retrospective stated preferences approach to assess the benefits of a coastal infrastructure investment in Barbados. Results show that the investment generated cultural and aesthetic ecosystem service benefits for tourists and residents, and that local businesses derived value and avoided some damage costs from the enhancement of regulatory ecosystem services. The approach is versatile facing data constraints and generates policy-relevant information to support decisions to scale up interventions, catalyze additional investment, and provide data on user preferences that can be incorporated in the design of future interventions.
hdl:11319/7849
Keywords: Q51; Q57; C51; F21; 330; ex-post analysis; impact evaluation; ecosystem services; stated preferences; contingent valuation; tourism; coastal infrastructure